Landslide hazard assessment and risk reduction in the rural community of Rampac Grande, Cordillera Negra, Peru - Jan Klimeš (2023)
This article describes the landslide risk assessment of the Rampac Grande rural community in the Peruvian Andes, where an unexpectedly fast-moving landslide claimed fatalities in 2009. The study site represents a socially, culturally, and geologically challenging environment that limits applicable technical solutions for landslide risk reduction and demands a high level of community participation in all risk reduction steps. The performed landslide surface movement monitoring and slope stability calculations showed that the studied slopes are very close to failure. Therefore, the detailed hazard assessment was combined with field investigations of household vulnerabilities to perform a qualitative risk assessment in the zone around the 2009 catastrophic landslide. Results show that the high vulnerability, rather than the very high hazard, is responsible for assigning houses to the high-risk classes and education or improvement of the households’ income is key for further risk reduction. This underlines the importance of vulnerability reduction through the collaboration of the community members with external actors (e.g., Peruvian experts), which was interrupted by the COVID-19 pandemic restrictions. The context of the performed landslide risk assessment provides a summary of the 12-year-long involvement of different actors in the landslide risk reduction effort and the evaluation of the effectiveness of the previously adopted mitigation measures. It suggests that the community perspective on the mitigation measures and its risk perception changes determine the long-term risk reduction outcomes.